Sharing research results: meanings and feelings in the return to the hospital - Gelman Constantin, Francisco; Sy, Anahí; Derossi, Paula; Sapienza, Cinthia; Moglia, Brenda (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
During the pandemic, as part of a transdisciplinary research project, we designed and developed the project "Transitioning from the pandemic to the post-pandemic: challenges and possibilities of new scenarios in public health, from the narratives of its workers" (PISAC-COVID 19 call), aimed at understanding the care experiences of health workers in the second level of complexity in the southern conurbation. In this framework, semi-structured interviews were conducted, aimed at recovering personal narratives, mostly at a distance, through virtual communication platforms and some in-person interviews. Towards the end of 2022, we had the opportunity to approach the hospitals to share the results of the analysis of those narrated experiences, in collective activities and already in a new socio-epidemiological reality.This paper seeks to analyze that experience of presenting results from the intersection of meanings and emotions that it generated: the recognition of workers in the conclusions enunciated as a form of validation of scientific knowledge, the dispute over the "moral/s" or lessons learned from the experience as premises for participation, transformation, or organization initiatives in the hospitals, the "catharsis" as a byproduct of the research process, the tensions between the voices recovered by the research and the voices authorized by institutional hierarchies. What does transdisciplinary research in public health on healthcare workers produce, and what can it produce? Who benefits from the knowledge produced? What specific contributions can this type of presentation experience make, compared to other instances arising from research of this kind, such as presenting results to academic peers, to officials, or in acts of tribute? What are the real possibilities for presenting results to authorities and workers? After the crisis, what time and openness do they have to listen to their own voices in a pandemic?